Biologic therapy practices in severe asthma; outcomes from the UK Severe Asthma Registry and survey of specialist opinion. Issue 2 (17th September 2022) - Mansur, Adel H.; Gonem, Sherif; Brown, Thomas; Burhan, Hassan; Chaudhuri, Rekha; Dodd, James W.; Pantin, Thomas; Gore, Robin; Jackson, David; Menzies‐Gow, Andrew; Patel, Mitesh; Pavord, Ian; et al.
Abstract: Background: Several biological treatments have become available for management of severe asthma. There is a significant overlap in the indication of these treatments with lack of consensus on the first‐line biologic choice and switching practice in event of treatment failure. Aims: To evaluate outcomes of biologic treatments through analysis of the UK Severe Asthma Registry (UKSAR), and survey of the UK severe asthma specialists' opinion. Methods: Patients registered in the UKSAR database and treated with biologics for severe asthma in the period between January 2014 and August 2021, were studied to explore biologic treatments practice. This was complemented by survey of opinion of severe asthma specialists. Results: A total of 2490 patients from 10 severe asthma centres were included in the study (mean age 51.3 years, 61.1% female, mean BMI 30.9 kg/m 2 ). Biologics use included mepolizumab 1115 (44.8%), benralizumab 925 (37.1%), omalizumab 432 (17.3%), dupilumab 13 (0.5%) and reslizumab 5 (0.2%). Patients on omalizumab were younger and had earlier age of onset asthma than those prescribed mepolizumab or benralizumab. Patients prescribed mepolizumab and benralizumab had similar clinical characteristics. Those on benralizumab were more likely to continue treatment at approximately one year follow‐up (93.9%), than those on mepolizumab (80%), or omalizumab (69.6%). The first‐choice biologic differed between centres and changed over the study time period. Experts' opinion also diverged in terms of biologic initiation choice and switching practice. Conclusion: We observed significant variation and divergence in the prescribing practices of biologics in severe asthma that necessitates further research and standardization.